Finding Audrey - Kinsella, Sophie 1969- (London Doubleday, 2015)
Fourteen-year-old Audrey is making slow but steady progress dealing with her anxiety disorder when Linus comes into the picture and her recovery gains momentum
Keywords: Anxiety disorders / Juvenile fiction; Friendship / Juvenile fiction; Anxiety disorders; Friendship; Verlieben; Weibliche Jugend; Film; Therapie; Angstbewältigung; Bruder; Familie; Panikreaktion; Freund; Jugendbuch; Jugendbuch